The Relationship Between Psychological Well-Being And Work Productivity Education Staff At Universitas Pembangunan Panca Budi - Nuraini Kemalasari Istiqamah; Hernawaty; Geby Citra Ananda (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the relationship between psychological well-being and the work productivity of education personnel at Universitas Pembangunan Panca Budi (UNPAB) Medan. Psychological well-being is a positive psychological condition that includes six main dimensions according to Ryff (1989), namely self-acceptance, positive relationships with others, autonomy, mastery of the environment, life goals, and personal growth. The research method used is quantitative correlational with a survey approach. The research population is all UNPAB education staff totaling 120 people, with a sample of 92 people determined using the Slovin formula. Data collection was carried out through the Scales of Psychological Well-Being (SPWB) questionnaire and work productivity scales that have been tested for validity and reliability. Data analysis used Pearson Product Moment correlation and simple linear regression. The results showed that there was a positive and significant relationship between psychological well-being and the work productivity of UNPAB education personnel (r = 0.712; p < 0.01), with a determination coefficient of 50.7%. The dimension of life goals and mastery of the environment are the strongest predictors of work productivity. The implications of this study emphasize the importance of psychological welfare improvement programs for education personnel to support the performance of institutions in a sustainable manner.